2012
DOI: 10.1007/s00468-012-0789-1
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of extreme climate events in Pinus sylvestris tree rings from Bulgaria

Abstract: Tree-ring studies may help better understand climate variability and extreme climate event frequency and are especially useful in regions where detailed meteorological records lack. We studied the effect of droughts and unusually cold periods on Pinus sylvestris tree-ring width and wood anatomy. Study sites were selected along an altitudinal gradient on Vitosha Mountain, Bulgaria. Drought conditions caused the formation of narrow tree rings or light rings if the drought occurred in July-August at the lower alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
4
18
1
1
Order By: Relevance
“…The above presented pattern of climate-growth relationship, namely the positive dominance of summer precipitation and negative impact of summer temperature was reported in other studies in Hungary on beech (Garamszegi & Kern, 2014) and on oak (Kern et al, 2013) and was observed many times on pine (Koprowski, 2012;Michelot, 2012;Panayotov et al, 2013;Levanič, 2015;Toromani et al, 2015) as well. However, we found a much unusual pattern also, which has never been observed in Hungary neither on pines nor on other species, but rare in the MJJ (May-June-July), JJA (June-July-August), SPR (March-April-May) and VGP (March-October) represent the combined periods, GWL shows groundwater data.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The above presented pattern of climate-growth relationship, namely the positive dominance of summer precipitation and negative impact of summer temperature was reported in other studies in Hungary on beech (Garamszegi & Kern, 2014) and on oak (Kern et al, 2013) and was observed many times on pine (Koprowski, 2012;Michelot, 2012;Panayotov et al, 2013;Levanič, 2015;Toromani et al, 2015) as well. However, we found a much unusual pattern also, which has never been observed in Hungary neither on pines nor on other species, but rare in the MJJ (May-June-July), JJA (June-July-August), SPR (March-April-May) and VGP (March-October) represent the combined periods, GWL shows groundwater data.…”
Section: Discussionsupporting
confidence: 76%
“…In the literature many types of radial growth features have been discussed like narrow rings (e.g. Panayotov et al, 2013), frost rings (e.g. Hantemirov et al, 2004), light rings (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research is in accordance with the findings of the other authors who found that the growth of Scots pine in the studied region mainly depends on the amount of available precipitation (Misi & Náfrádi, 2016) or severity of drought (Misi & Ná-frádi, 2017) and less on temperature (Sidor & Popa, 2015). Some authors found an indirect connection between climate and growth of Scots pine -Poljanšek et al (2015) found a close connection between a hot and dry summer and the number of needles of the terminal bud, while Panayotov et al (2012) found a connection between drought and partial or complete absence of latewood if the summer in the year of ring formation was dry and warm.…”
Section: Discussion Correlation Between Growth and Spimentioning
confidence: 99%
“…MorenoGutiérrez et al, 2012;Olivar et al, 2012;Novak et al, 2013), P. pinaster (e.g. Rozas et al, 2011;Campelo et al, 2013) and P. sylvestris (Panayotov et al, 2013), have shown good correlations between IADF formation and climate around the Mediterranean. The consistency of the climatic signal among different pine species and areas suggests that a large-scale network of IADFs could be developed in the Mediterranean region to study intraannual climate variability (Campelo et al, 2013).…”
Section: Study Areamentioning
confidence: 95%